2017
DOI: 10.1002/mbo3.490
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of aromatic hydroxylating dioxygenase genes in mangrove microbiome and their biogeographic patterns across global sites

Abstract: Aromatic hydrocarbons (AH), such as polycyclic aromatic hydrocarbons, are compounds largely found in nature. Aromatic‐ring‐hydroxylating dioxygenases (ARHD) are proteins involved in AH degradation pathways. We used ARHD functional genes from an oil‐impacted mangrove area and compared their diversity with other sites around the world to understand the ARHD biogeographic distribution patterns. For this, a comprehensive database was established with 166 operational protein families (OPFs) from 1,758 gene sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…These metabolic pathways were presented at these sites (Cabral et al, 2018). Recently, genes encoding aromatic hydroxylating dioxygenase genes were detected in the same oil-impacted areas used at this study (BrMgv02) using a clone library and metagenomic/metatranscriptomic methodology (Sousa et al, 2017;Cabral et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…These metabolic pathways were presented at these sites (Cabral et al, 2018). Recently, genes encoding aromatic hydroxylating dioxygenase genes were detected in the same oil-impacted areas used at this study (BrMgv02) using a clone library and metagenomic/metatranscriptomic methodology (Sousa et al, 2017;Cabral et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that microorganisms from the Pseudomonas group had a big pathway of degradation for many types of pollutants [34]. This microbial group can degrade a wide variety of hydrophilic and hydrophobic compounds, including polycyclic aromatic hydrocarbons (PAHs) [35][36][37]. On the other hand, Bacillus, Rhodococcus, and Actinomyces strains can also degrade PHAs [37][38][39].…”
Section: Microbial Growth In the Lab-scale Bioreactors And Preliminarmentioning
confidence: 99%
“…This microbial group can degrade a wide variety of hydrophilic and hydrophobic compounds, including polycyclic aromatic hydrocarbons (PAHs) [35][36][37]. On the other hand, Bacillus, Rhodococcus, and Actinomyces strains can also degrade PHAs [37][38][39]. The isolated strains from the soils of the three types of experiments were cultivated in M9 minimum agar added with FO6, in order to observe if they can use TPH present in FO6 as carbon source (Figure 5).…”
Section: Microbial Growth In the Lab-scale Bioreactors And Preliminarmentioning
confidence: 99%
“…The strains of the genus Variovorax are widely distributed in nature, from temperate to Polar regions, and some members are psychrophilic [7,8]. They were isolated from a variety of ecological habitats, including Antarctic lichen, plant rhizosphere, sewage, and contaminated soil with chemicals [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits diverse metabolic features. More importantly, it is known for its metabolism of organic pollutants, including PAHs and chlorophenol [7,11]. Recently, Ghimire et al reported that Variovorax sp.…”
Section: Introductionmentioning
confidence: 99%